Design, synthesis and characterization of tracers and development of a fluorescence polarization immunoassay for the rapid detection of ractopamine in pork. (15th January 2019) - Dong, Baolei; Zhao, Sijun; Li, Hongfang; Wen, Kai; Ke, Yuebin; Shen, Jianzhong; Zhang, Suxia; Shi, Weiming; Wang, Zhanhui
Highlights: New fluorescein-labeled ractopamine were synthesized and selected to improve sensitivity. A highly sensitive and specific FPIA for screening ractopamine in pork was developed. The specificity of the FPIA was evaluated with 70 β-agonists and β-blockers. The highly accurate and precise FPIA was applied to screen real pork samples. Abstract: In this study, 10 fluorescein-labeled ractopamine (RAC) derivatives (tracers) were synthesized and characterized to develop a rapid fluorescence polarization immunoassay (FPIA) for the detection of RAC in pork, using previously produced RAC polyclonal antibodies. The effect of the tracer structure on the sensitivity of the FPIA was investigated. The specificity of the FPIA was evaluated with 70 β-agonists and β-blockers. The FPIA showed a limit of detection of 0.56 μg kg −1 for RAC in pork, with recoveries ranging from 74.8% to 86.6% in spiked samples. The total analysis time, including sample pretreatment, was less than 1 h. The FPIA was used to screen 150 commercial pork samples for RAC residues and the results were consistent with those of an enzyme-linked immunosorbent assay (ELISA) and ultra-high-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS). Our results demonstrate that the FPIA developed here is a rapid, accurate, and sensitive screening method for RAC residues in pork.